Discovering the material palette of the artist: a p‐XRF stratigraphic study of the Giotto panel 'God the Father with Angels'. (17th February 2017) - Galli, A.; Caccia, M.; Alberti, R.; Bonizzoni, L.; Aresi, N.; Frizzi, T.; Bombelli, L.; Gironda, M.; Martini, M.
Abstract : Elemental analysis, and in particular stratigraphic distribution of elements themselves, is a fundamental method to address the composition of materials, but its nature, often invasive, crashes with the necessity of avoiding artefacts' damage when dealing with Cultural Heritage objects. In fact, when work of art are involved, sampling is often forbidden, and transferring an artistic artefact to equipped laboratories is a not negligible issue. The skill to employ in situ non‐destructive and non‐invasive analytical method is essential. In this scenario, portable X‐ray fluorescence (p‐XRF) has become one of the most employed techniques due to the development of adaptable and open architecture instruments. In this paper, we show a new data analysis protocol and its application to XRF data acquired from a work by Giotto never studied before: 'God the Father with Angels' (ca. 1330, San Diego Museum of Art). The measurements have been performed in situ during the closing time of the exhibition 'Giotto, l'Italia' (Milano Palazzo Reale – 2 September 2015/10 January 2016). Combining the effectiveness of scanning p‐XRF with the responsive of image spectroscopic analysis, we move step by step toward the discovery of Giotto's palette for the flesh tones in God the Father with Angels; our method allows to argue the stratigraphy of the painting without complementary measurements and, at the same time, provides a sequential and smart representation of complex data. Copyright © 2017 John Wiley & Sons, Ltd.